(untitled) (Research, Society and Development, 2023)
The objective was to evaluate and describe the main orofacial injuries resulting from physical and sexual violence in children and adolescents, considering that, due to their greater vulnerability, they are habitual victims of abusive acts. The present study is configured as an integrative review of the literature. The bibliographic survey was carried out through online access to BVS Brasil and Pubmed, in portuguese, english and spanish, without defining time, considering the age range of 0-19 years. Of thirty-seven articles evaluated, only three were included in the research, when all eligibility criteria were applied. Through the results obtained, the study observed the presence of orofacial manifestations in cases of violence, compromising soft and hard tissues of the face and oral cavity. It can be concluded that physical and sexual violence against children and adolescents is associated with the presence of orofacial manifestations. However, more studies on the topic are needed for an accurate comparison.